Conjugation of Skills to learn in the development of university students - Garza Puente, Diana Guadalupe (Universidad Autónoma de Tamaulipas, 2018)
Culture and education directly affect the exercise of skills in young people, hence the need to take a teaching responsibility focused on the development of the same, exercising educational methodology based on competencies considering factors that condition such event: personal characteristics, psychological, demographic; These skills allow not only skills and talents on a personal level, but also a professional one affecting the entire educational stage, therefore, educational training in this aspect is paramount, that is, final results referred to in productivity through mental process bridges applied to adaptive teaching. Behavioral skills in multidimensional aspects affected by the development of soft skills associated with learning skills, supported these days with continuous education e-learning prepare the student for life, conjugated the knowledge of meaningful learning. The design of professional curricular proposals based on models of professionalization of a productive system demand technical, systematic, relational and contingency response dimensions, requiring the student’s skills, abilities, attitudes and necessary knowledge that reflect the obtaining of competences obtained from the teaching process-learning; therefore, the need to identify and relate the skills to learn in the development of university students as part of their identity.